Leading Research and Innovation - Malvar, Henrique S. (IEEE Signal Processing Magazine, 2006)
The author of this article has made many contributions to academic and industrial research in signal processing, especially in multirate systems and signal compression. Henrique (Rico) Malvar is a director of the Microsoft Research (MSR) main lab in Redmond, Washington. His management career started very early, as he says, by “learning to swim by being thrown in deep water.” He shares with us some of his experience, with emphasis on leadership lessons he learned. He also shares some of the culture at MSR and how leadership concepts are applied to his management of many research groups at the MSR Lab. Rico closes with some additional tidbits for effective leadership, which we hope will inspire our readers.